Ultrasonic measurement and elastic properties of the PbO-SrO-B2O3 glass system - Moya, Bianca Reis; Reis, Idalci Cruvinel Dos; Reynoso, Victor Ciro Solano [UNESP]; Barros, Mariana Da Silva; Gomes, Kamila Ruthielle Silva (IBRACON - Instituto Brasileiro do Concreto, 2020)
The PbO-SrO-B2O3 glass system with the of molar ratio of R (= PbO/B2O3) were prepared by fusion method. The elastic properties have been investigated using longitudinal and transversal ultrasonic wave velocity. Measurements were performed at room temperature and using pulse-echo technique at frequency of 5 MHz. The results indicate that, when increasing R value, the glass network stability decreases. This decrease indicates, of the increase the number of borate structures with non bridging oxygen (NBOs) at the expense of the decrease of borate units with tetrahedral structures. This feature may lead to the more open glass network structures and lower stiffness of the samples studied.

Vidros do sistema PbO-SrO-B2O3, em função da razão molar R (=PbO/ B2O3), foram preparados usando a técnica de fusão. As propriedades elásticas tem sido investigadas a partir das medições das velocidades longitudinais e transversais das ondas ultrassônicas. As medidas foram realizadas a temperatura ambiente usando a técnica de pulso-eco a 5 MHz. Os resultados indicam que, com o aumento do valor de R, a estabilidade da rede do vidro diminui. A diminuição da estabilidade da rede vítrea indica o aumento do número de estruturas boratos com oxigênios não ligados às expensas da diminuição das unidades boratos com estruturas tetraédricas. Esta característica pode levar à ter no vidro estruturas mais abertas e a ter menor rigidez das amostras estudadas.
Medidas ultrassônicas e propriedades elásticas do sistema vítreo PbO-SrO-B2O3
Keywords: vidro; método de fusão; densidade; medidas ultrassônicas; glass; fusion method; density; ultrasonic measurements